Factors associated with mobile phone ownership and potential use for rabies vaccination campaigns in southern Malawi - Orla Marron; Gareth Thomas; Jordana L. Burdon Bailey; Dagmar Mayer; Paul O. Grossman; Frederic Lohr; Andy D. Gibson; Luke Gamble; Patrick Chikungwa; Julius Chulu; Ian G. Handel; Barend M. de C Bronsvoort; et al. (BMC, 2020)
Abstract Background Rabies is a fatal but preventable viral disease, which causes an estimated 59 000 human deaths globally every year. The vast majority of human rabies cases are attributable to bites from infected domestic dogs and consequently control of rabies in the dog population through mass vaccination campaigns is considered the most effective method of eliminating the disease. Achieving the WHO target of 70% vaccination coverage has proven challenging in low-resource settings such as Sub Saharan Africa, and lack of public awareness about rabies vaccination campaigns is a major barrier to their success. In this study we surveyed communities in three districts in Southern Malawi to assess the extent of and socio-economic factors associated with mobile phone ownership and explore the attitudes of communities towards the use of short message service (SMS) to inform them of upcoming rabies vaccination clinics. Methods This study was carried out between 1 October-3 December 2018 during the post-vaccination assessment of the annual dog rabies campaign in Blantyre, Zomba and Chiradzulu districts, Malawi. 1882 questionnaires were administered to households in 90 vaccination zones. The surveys gathered data on mobile phone ownership and use, and barriers to mobile phone access. A multivariable regression model was used to understand factors related to mobile phone ownership. Results Most survey respondents owned or had use of a mobile phone, however there was evidence of an inequality of access, with higher education level, living in Blantyre district and being male positively associated with mobile phone ownership. The principal barrier to mobile phone ownership was the cost of the phone itself. Basic feature phones were most common and few owned smartphones. SMS was commonly used and the main reason for not using SMS was illiteracy. Attitudes to receiving SMS reminders about future rabies vaccination campaigns were positive. Conclusions The study showed a majority of those surveyed have the use of a mobile phone and most mobile phone owners indicated they would like to receive SMS messages about future rabies vaccination campaigns. This study provides insight into the feasibility of distributing information about rabies vaccination campaigns using mobile phones in Malawi.